Adoption of cleaner production concept in hawker centre / Lee Shei Ching - Lee, Shei Ching (2021)
Hawker centres are commonly found in Malaysia and the facilities operations may contribute to significant fraction of carbon footprint from food industries. In this work, Cleaner Production (CP) audit was conducted at a hawker center to quantify the energy usage, fuel and resources consumption, raw material usage and generation of waste. A hawker centre located at Kepong, Kuala Lumpur was selected to identify the Cleaner Production (CP) Strategy that aims to produce a greener hawker. According to the audit finding, the normal operation of hawker centre generates 1.18kg CO2 per customer which were contributed by 53% food waste, 28% LPG fuel consumption and 14% electricity usage. The remaining are contributed by 6% of solid waste and 2% is by the wastewater production and water usage. From the findings, a total of 30 CP options were identified with 18 of it were suggested for cleaner production implementations based on considerations of the cost and improvement in carbon emission reduction. Through the carbon footprint calculation, the implementation of the CP options cut the carbon emission from 1.18 kgCO2 to 0.82kgCO2 per customer which equivalent to 31% of reduction. The estimated investment cost required for the implementations of suggested CP options is sixteen thousand Ringgit Malaysia with payback period of 1 year and 3 months. Therefore, implementation of CP options was beneficial to reduce carbon emission and produce a greener hawker.